A multimodal educational intervention study on perception and practices of menstruation and menstrual hygiene among tribal adolescent girls from a residential school in H. D. Kote taluk of Mysuru district - Chitharagi, Vidyavathi B.; M., Raghavendra Rao; Bhat, Deepa; Urs, Tejashree Anantharaj; S., Divya K.; Kumar, Sunil; S., Krishna Karthik M. V. (International Journal Of Community Medicine And Public Health, 2025)
Background: Educating girls about menstruation from an early age could empower them with the knowledge and confidence to manage their periods safely and hygienically. This education could also help dispel myths and cultural taboos surrounding menstruation, such as the idea of impurity, which can lead to social stigmatization and discrimination against menstruating individuals. By ensuring that girls receive comprehensive and accurate information about menstruation from a young age, we can help them adopt safer and healthier practices while also addressing the stigma and misconceptions surrounding menstruation. This education would not only benefit individual girls but also contribute to the overall well-being and empowerment of women worldwide. Methods: This multimodal interventional study is aimed in assessing the perception and practices of menstruation and menstrual hygiene among school going tribal adolescent girls in Mysuru district. By focusing on a residential school and a pre-university college, the intervention targeted key phases in the educational journey of the students, aiming to foster development, improve outcomes, and provide insights into the menstrual hygiene and their practices among tribal youth in this region. Results: The pre- and post-interventional data reveal a significant improvement in menstrual health knowledge and practices. Prior to the intervention, misconceptions were evident, such as confusion about the source of menstrual blood and inappropriate practices during menstruation. Conclusions: The complete adoption of recommended practices and the elimination of outdated restrictions highlight the success of the intervention in promoting better menstrual health. Continued educational efforts are essential to sustain these improvements and address any remaining gaps in menstrual health knowledge and practices.